Who Should Get Money? Estimating Welfare Weights in the U.S. - Francesco Capozza; Krishna Srinivasan (Center for Economic Studies and ifo Institute (CESifo), 2024)
Evaluating the desirability of a reform typically involves weighing the gains of the winners against the losses of the losers using welfare weights. Welfare weights measure the value that citizens assigns to a 1 gain in consumption to individuals. They can capture various normative ideals like utilitarianism and equality of opportunity. What are the welfare weights that citizens assign to individuals in society? We develop a portable method to elicit welfare weights from general population samples and validate it using two experiments. We find that the general population weights are more progressive than the weights implied by tax and transfer policies in the U.S., indicating that the general population desires additional redistribution. The general population weights are less progressive than those frequently used in the literature. We explore the implications of these weights for optimal income taxes.
Keywords: C93; D31; H23; I31; 330; welfare weights; policy views; income taxation